PEMBELAJARAN BERBASIS PRAKTIKUM BERVISI SETS UNTUK MENINGKATKAN KETERAMPILAN LABORATORIUM DAN PENGUASAAN KOMPETENSI - Baeti, Shinta Nur; Binadja, Achmad; Susilaningsih, Endang (Jurnal Inovasi Pendidikan Kimia, 2014)
This research aims to produce innovation of performance assessment rubric on practicum salt hydrolysis material. The rubric was being consulted and validated by experts, then it was being revised and tested. The trial result was being analyzed and revised, then usage test was given. The research was conducted at SMA in Semarang using purposive sampling technique. A small scale was given to ten students and large scales were given to the students in class XI IPA 3 and XI IPA 4. The results showed that the validity of innovation of performance assessment rubric by experts was 86.46%. Implementation innovation of performance assessment rubric on practicum salt hydrolysis "test salt solution in water", the agreement has been reached between the observer and the student with the value of generalizability coefficient are 0.711 and 0.744. The impact of the use of performance assessment rubric is that the cognitive learning outcomes of the students can achieve mastery learning. In class XI IPA 3, there are 33 students from 38 students achieve KKM and in class XI IPA 4 there are 33 students from 37 students achieve values KKM. Student’s characters can also be developed during lab activities, such as discipline, honesty, independence, curiosity, responsibility, and cooperation. Based on the results, innovation of performance assessment research practicum salt hydrolysis "test salt solution in water" could be used as a guide to the performance assessment (psychomotor) of the students and increase understanding of the concept and fosters student’s character. Keywords : Innovation, Performance Assessment Rubric, Salt Hydrolisis